Micropallet arrays with poly(ethylene glycol) walls - Wang, Yuli (2008)
Arrays of releasable micropallets with surrounding walls of poly(ethylene glycol) (PEG) were fabricated for the patterning and sorting of adherent cells. PEG walls were fabricated between the SU-8 pallets using a simple, mask-free strategy. By utilizing the difference in UV-transmittance of glass and SU-8, PEG monomer was selectively photopolymerized in the space surrounding the pallets. Since the PEG walls are composed of a cross-linked structure, the stability of the walls is independent of the pallet array geometry and the properties of the overlying solution. Even though surrounded with PEG walls, the individual pallets were detached from the array by the mechanical force generated by a focused laser pulse, with a release threshold of 6 μJ. Since the PEG hydrogels are repellent to protein adsorption and cell attachment, the walls localized cell growth to the pallet top surface. Cells grown in the microwells formed by the PEG walls were released by detaching the underlying pallet. The released cells/pallets were collected, cultured and clonally expanded. The micropallet arrays with PEG walls provide a platform for performing single cell analysis and sorting on chip.